2018
DOI: 10.1038/s41598-018-32517-9
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic assessment of chemotherapy and Smac mimetic drugs in cells with defective DNA damage response pathways

Abstract: DNA damaging therapies can spur the formation of therapy-related cancers, due to mis-repair of lesions they create in non-cancerous cells. This risk may be amplified in patients with impaired DNA damage responses. We disabled key DNA damage response pathways using genetic and pharmacological approaches, and assessed the impact of these deficiencies on the mutagenicity of chemotherapy drugs or the “Smac mimetic” GDC-0152, which kills tumor cells by targeting XIAP, cIAP1 and 2. Doxorubicin and cisplatin provoked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…SM-mediated killing has been attributed to endogenous TNF in cancer cells 45 , 46 ; however, it has been reported to be independent of TNF in some cancer cells 60 and HIV-infected T cells 32 . While TNF-mediated SM-induced killing in U1 undifferentiated and PMA-differentiated cells, it was not observed in primary MDMs.…”
Section: Discussionmentioning
confidence: 99%
“…SM-mediated killing has been attributed to endogenous TNF in cancer cells 45 , 46 ; however, it has been reported to be independent of TNF in some cancer cells 60 and HIV-infected T cells 32 . While TNF-mediated SM-induced killing in U1 undifferentiated and PMA-differentiated cells, it was not observed in primary MDMs.…”
Section: Discussionmentioning
confidence: 99%
“…Smac mimetics are commonly used in vitro to activate necroptotic pathways when combined with TNFα and an inhibitor that targets caspase-8, so we used this approach to specifically interrogate the mutagenic potential of necroptotic signaling. We observed that sublethal exposure to Smac mimetics without concurrent TNFα treatment was non-mutagenic 34,50 . We recently discovered that those treatments triggered a lytic, non-apoptotic and non-necroptotic mode of death 32 .…”
Section: Discussionmentioning
confidence: 87%
“…This feature may be especially beneficial for cancer patients with germline flaws in DNA damage response pathways, for whom mutagenic therapies would be particularly risky. As yet, no anti-cancer agents have been created that exclusively trigger necroptosis, but Smac mimetic treatment (which can provoke apoptotic or necroptotic cell death) was non-mutagenic in vitro, even when accurate DNA repair was compromised [ 199 ]. Further research will be needed to define the mutagenicity associated with sublethal activation of more recently described cell death pathways, including pyroptosis and ferroptosis, and the prospects for therapeutic exploitation of these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…H2AX was phosphorylated primarily by DNA-PK following TRAIL treatment [ 160 ]. Mutation frequencies were dramatically reduced in DNA-PKcs-deficient cells following exposure to chemotherapies doxorubicin and cisplatin, and vincristine, the mutagenesis of which was caspase/CAD-dependent [ 199 ]. This further highlights the mutagenic potential of NHEJ machinery and also directly implicates the requirement of error-prone repair pathways in CAD mutagenesis.…”
Section: Mutagenic Consequences Of Apoptotic Signalingmentioning
confidence: 99%